Naturalism - Goetz, Stewart; Taliaferro, Charles 1952- (Grand Rapids, Mich [u.a.] Eerdmans, 2008)
The challenge of strict naturalism -- Strict naturalism versus a natural view of persons -- Naturalism and the soul -- Naturalism, consciousness, and values -- Beyond naturalism -- Appendix : the argument from reason
The challenge of strict naturalism -- Strict naturalism versus a natural view of persons -- Naturalism and the soul -- Naturalism, consciousness, and values -- Beyond naturalism
Includes bibliographical references (p. 123-129) and index
Archivierung prüfen
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Naturalism -- Religious aspects -- Christianity; Apologetics